Chinese Debates on the Democratization Process - Peer Møller Christensen (Journal of China and International Relations, 2014)
The new economic importance of the Chinese economy has created Chinese expectations that the country will be able to regain a political and cultural position in the world in accordance with this economic status. But for China to become a respected member of world society, one of the most severe obstacles is its, from a western perspective, undemocratic political system. The article describes the lively debate going on among Chinese intellectuals of diverse political-ideological convictions about what kind of democracy should be the model for China’s future political system. The liberally oriented intellectuals want a political system very much like American liberal constitutional democracy, while intellectuals on the left side of the political spectrum want a democracy with a clear socialist basis. Although Chinese intellectuals form a minority in society, these intellectual debates are sure to have influence on both public opinion and opinions and attitudes among political decision makers inside the Chinese Communist Party. Further investigations will have to establish to what degree the perceptions of China's political future and democratization are reflected in the political attitudes among the Chinese in general, and how they are perceived inside the confines of political decision making in the Chinese Communist Party. Only then will it be possible to answer the questions: "What kind of democracy do the Chinese want?" and "What kind of democracy are the Chinese going to get?"